IoT based Car Parking System using LoRaWAN Technology for CIT Campus - Poongothai, M.; M.N, Chinmaya Mahadev.; Shivananth.A,; D, Vamsi Krishna; R, Vinesh. S. (Journal of ISMAC, 2023)
The usage of four-wheeler vehicles has increased over time, and finding a parking spot to park the cars in is getting much more challenging. This issue also exists on the CIT CAMPUS, which led to developing a parking system using IoT technology to make it simpler to find parking places. An IoT-based car parking system based on LoRaWAN technology is suggested as a solution to this issue. The purpose of this research is to design and implement a well-organised parking system with a user-friendly application which can avoid cramming in the car parking area. In the proposed system, Arduino-LoRa transmitter boards, Ultrasonic sensor and LG01-LoRa gateway are used for the implementation. Ultrasonic sensor-equipped Arduino-LoRa transmitter boards are positioned in various parking lots. It is used as a processing element which detects the availability of parking space in the parking area and transmits the data to the gateway that is situated close to the parking lots. The data is received by the gateway and forwards the slot information to the Things Network. The vacant spaces in the parking area could be viewed using a mobile application. The proposed system includes a gate entry management system that reads the number plate of a vehicle using YOLO- V3 algorithm and stores the real-time vehicle log information in the database. This method makes it easier for drivers to identify the available parking spaces offering a streamlined parking experience, which helps users spend less time in parking their cars.
Keywords: Internet of Things; LoRaWAN Technology; Arduino UNO Processor; The Things Network; Sensor System and LoRa Gateway